Does 3D Ultrasound Enhance the Diagnosis of Bladder Tumours in Patients with Haematuria?. (7th March 2012) - Silva-Ramos, Miguel; Louro, Nuno; Versos, Rui; Cavadas, Victor; Marcelo, Filinto
Abstract : Purpose . Bladder cancer is a frequent cause of haematuria in elderly patients, and bladder ultrasound (US) is a valuable tool in diagnosing these malignancies. We examined the accuracy of 3D bladder US in diagnosing bladder tumors in patients with haematuria. Patients and Methods . Twenty-one patients observed in the emergency department for haematuria underwent a kidney and bladder US. Patients with normal or uncertain bladder US findings underwent a 3D US and a cystoscopy. Results . In 5 (23.8%) patients, the 3D US detected bladder tumours not seen in 2D US. All these patients were found to have bladder tumours on cystoscopy. Another 5 (23.8%) patients with uncertain findings on 2D US had normal 3D US and cystoscopy. 3D US showed a sensitivity of 83.3% and a specificity of 100% with a positive predicted value and negative predictive values of 100% and 93.8%, respectively. Conclusion . 3D US was more sensitive than 2D US in diagnosing bladder tumours in patients with haematuria.